Right ventricular dysfunction in stress cardiomyopathy: The prognostic value of fractional area change. Issue 9 (20th August 2020) - Subramanian, Muthiah; Ahamed, Hisham; Reddy, Chirag; Mathew, Navin; Chandrasekhar, Rajiv
Abstract: Background: There are limited data on the impact of right ventricular dysfunction (RVD) on the clinical outcomes in patients with stress cardiomyopathy (SC). The purpose of this study was to evaluate the impact of RVD on outcomes and to characterize the prognostic value of RV fractional area change (FAC). Methods: This study retrospectively analyzed data from 111 consecutive patients with SC. The primary endpoint, major cardiac events (MCE), was a composite of 30‐day mortality, cardiogenic shock, life threatening arrhythmias, and stroke. Regression analysis was used to identify independent predictors of short (30 days)‐ and long‐term MCE. Results: Among the 111 patients (80.2% females, mean age 45.8 ± 11.5 years), RVD was present in 17(15.3%) patients. MCE occurred in 18(16.2%) and 22(19.8%) patients at 30 days and during long‐term follow‐up, respectively. RVD was an independent predictor of short (HR 1.88(1.21–15.67), P = .036)‐ and long (HR 1.65(1.11–9.67), P = .016)‐term MCE. Compared with tricuspid annular plane systolic excursion < 15 mm (TAPSE) (sens 72.2%, spec 94.1%, AUC 0.75) and tricuspid annulus pulsed TDI‐derived peak systolic velocity (S′) < 9.5 cm/s (sens 67.2%, spec 94.5%, AUC 0.72), RV FAC < 30% (sens 89.1%, spec 100%, AUC 0.92) had the highest accuracy and discriminative ability to predict MCE. Furthermore, RV FAC < 30% was a significant predictor of recurrence (29.4% vs 2.1%, P = .002) and delayed recovery time (21.4 ± 6.8 vs 8.5 ± 4.3 days, P < .001). Conclusions: The presence of RVD in stress cardiomyopathy identifies patients at higher risk of mortality, complications, delayed recovery, and recurrence. Compared with other indices, RV FAC has the highest prognostic ability to predict these outcomes.